Synthesis of graphene from food and agricultural wastes in ubon ratchathani province, thailand - Ruaysap, Makabodee; Pongphai , Tontrakarn; Sirilapphokhin , Kanya; Sirilapphokhin, Prin; Tipparach, Udom (Indochina Applied Sciences, 2022)
This research aims to investigate the possibility of synthesis of graphene from food and agricultural waste materials by Chemical Vapor Deposition (CVD). The starting materials including coconut shells and cricket legs were used to synthesize graphene. The synthesized graphene specimens were characterized by Ultraviolet-visible spectroscopy (UV-Vis), Powder X-ray diffraction (XRD) technique, Dispersive Raman spectroscopy, SEM, and TEM. Both resultant graphene samples: coconut shells and cricket legs showed graphene characteristics with the maximum wavelength of UV spectrum of synthesized graphene in ethanol at ~244 nm comparable with a standard graphene. The graphene characteristics of coconut shells and cricket legs were also confirmed by XRD showing (002) peak at 2θ≈26°. The SEM images showed lamella structure and wrinkle texture, demonstrating the multilayered microstructure and crumpled sheets and folded sheets. The TEM images also confirmed the layered sheets restacking structure with the different numbers of sheets and expressed that the graphene is a semitransparent material. Data obtained from Raman spectroscopy indicated that the defect of structure band or D-band at 1,340 – 1,380 cm–1, the graphite band or G-band at 1,500 – 1,600 cm–1 corresponding to sp2 of carbon atom, the graphene band or 2D-band at 2,500 – 2,600 cm–1 showing that the structure of graphene is a multilayer with small sizes and the overtone band of graphite or 2G - band at 3,100 – 3,200 cm–1. On the basis of the result, graphene was possibly synthesized from coconut shells and cricket legs.